Detection of Hepatitis E Virus and Toll-Like Receptor 4 (rs4986790 and rs4986791) Genotypes Among A Sample of Hemodialysis Patients - Haleema Salih; Ahmed Abbas (The Iraqi Journal of Medical Sciences)
Background: Hepatitis E virus (HEV) is one of the prevalent nosocomial transmitted agents among patients on maintenance hemodialysis. Innate immunity's main actors, Toll-like receptors (TLRs), are able to identify the chemical patterns linked to pathogens. Objective: To investigate the seroprevalence of HEV in hemodialysis (HD) patients and study the TLR4 polymorphism (rs4986790 and rs4986791) in association with HEV in HD patients. Methods: One hundred and fifty patients on maintenance HD attending the HD centers of Al-Karama Hospital and Al-Yarmouk Teaching Hospital in the period from March to November 2021. Using enzyme-linked immunosorbent assay (ELISA) kit, serum samples were examined for the existence of anti-HEV (IgG and IgM) antibodies and conformation by using molecular technique quantitative reverse transcription polymerase chain reaction (qRT-PCR). The selected single nucleotide polymorphisms (SNPs) (rs4986790 and rs4986791) in TLR4 were amplified by using conventional PCR and then confirmed by sequencing their polymorphism. Results: Out of 150 hemodialysis patients, the seropositive result for HEV-IgG and IgM was 10 and 6, respectively. While 14 patients were positive by PCR. On the other hand, the result of IgM was negative for all control group. The analysis of TLR4 rs4986790 SNPs were 24 (80%) AA and 6 (20%) AG in patients while 6 (60%) AA and 4 (40%) AG in control group with insignificant difference. In addition, the TLR4 rs4986791 SNPs were 24 (80%) CC and 6 (20%) CT in patients while 6 (60%) CC and 4 (40%) CT in control group with insignificant difference. Conclusion: Patients undergoing HD are susceptible to HEV infection, the sero-prevalence of HEV in patients considered as risk factor. The genotypes of TLR4 SNPs (rs4986790 and rs4986791) have no significant association with HEV in HD patients. Keywords: HEV, seropositivity, hemodialysis, TLR4 Citation: Salih HS, Abbas AA. Detection of hepatitis E virus and toll-like receptor 4 (rs4986790 and rs4986791) genotypes among A sample of hemodialysis patients. Iraqi JMS. 2023; 21(1): 145-153. doi: 10.22578/IJMS.21.1.16